Creep lifetime prediction of 9Cr-1Mo (grade T91) steel via small punch creep tests and hierarchical multiscale analysis. (1st November 2020) - Nguyen, Vinh Phu; Ibupoto, Fahim Ahmed; Pham, Li Qui; Choi, Woosung; Shin, Keesam; Kim, Bum Joon; Kim, Moon Ki; Choi, Seung Tae
ABSTRACT: In this study, the creep deformation of ferritic/martensitic 9Cr-1Mo (Grade T91) steel boiler tubes that occurs during the operation of thermal power plants is studied using crystal elasto-viscoplasticity finite element analysis (CEV-FEA). The material properties and creep behaviour of Grade T91 were obtained through experimentation and computational analysis at different scales, e.g., molecular dynamics simulation, scanning electron microscopy, small punch (SP) tests. A triple junction of grains with various combinations of crystallographic orientations of polycrystalline Grade T91 was also simulated by CEV-FEA to investigate the stress concentration evolution during creep deformation. The stress concentration at the triple junction was then used as an input for the creep cavitation model, i.e., as the representative stress driving creep cavitation. The combination of CEV-FEA and SP test experiments can improve the evaluation of creep lifetime for as-received boiler tubes with minimum requirements for the amount of material and testing time.